Using Support Vector Machines for Predicting and Mitigating Stunting in Early Childhood Education in Rural Semarang - Suamanda Ika Novichasari; Alifia Revan Prananda; Dhanang Suwidagdho; Syifa Fauziah; Vania Amelia Setya Wijaya; Otmar Shah Adam (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
In 2030, 70% of Indonesia's population will be of productive age (15-64 years), which is a demographic bonus. However, this potential is threatened by the high rate of stunting in children, which threatens future workforce productivity. Early identification of stunting risk is essential for timely intervention. This study develops a stunting prediction model using machine learning with data from early childhood education institutions in rural Semarang. The model used is aÂ Support Vector Machine (SVM) implemented through the RapidMiner framework. The SVM model achieved an accuracy of 97.56%, a precision of 98.97%, aÂ recall of 97.37%, and an AUC of 0.997. The results of the SVM model highlight the importance of physical motor skills and artistic development.